GIS Implementation to Create a Map for Waste Container Sites in Banda Aceh, Indonesia - Muhammad Zikrullah (Winaya Inspirasi Nusantara Foundation, 2023)
The capital of Aceh Province, Indonesia, Banda Aceh, has experienced a number of problems with the handling of municipal solid waste due to an increasing urban population. Problems with waste management are also getting worse as a result of inadequate infrastructure and ineffective solutions. Waste containers/bins are the most basic items that can be used to solve issues with waste management. In this study, data from nine subdistricts of Banda Aceh had been gathered for waste dump locations from to analyze the spatial distribution of waste bins. Through the generalization tool in ArcGIS Pro, a spatial variation of distance between the trash cans was discovered. Changing the waste management system requires the application of geospatial approaches on a global scale. In the region of attention, this study evaluated the appropriate distance for waste container placement and the results were used to produce a number of maps showing the various sites where the waste container should be placed for the Banda Aceh government.